Implementation of IoT-Based Hydroponics for SLB Pembina Pekanbaru students - Yulisman Yulisman; Uci Rahmalisa; Khusnul Fikri; Arie Linarta (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Special schools are special schools for children with special needs who aims to provide opportunities for children in obtaining education. SLB Pekanbaru Pembina State is a special education and special service (PK-LK) which has goals and targets to a) Produce students who are able to compete in this era of globalization globalization b) Produce students who are able to apply the utilization of science and technology optimally. This school handles students who have mental and physical limitations and intellectuals or called with disabilities, this school is located at Jalan Segar No. 46 Rejosari Village, Tenayan Raya District, Pekanbaru City, was founded by the Ministry of Education and Culture National Education in 1998, the Decree on the Appointment of the Pembina State SLB was issued by Minister of National Education No.13a/O/1998. On January 29, 1998, SLB Negeri The supervisor of Pekanbaru is currently led by Mr. Moelya Eko Suseno, S.Kom, M.TI, M.Pd. This school has teacher educators from graduates of Special Education (S1, S2 and even S3) the current number of SLB teachers is 55 people (all majors of visual impairment), administrative staff 7 people. For students from the level (SDLB, SMPLB and SMALB) totaling 367 people (all disabilities). The development of the Pekanbaru Pembina State SLB from year to year experienced an increase, especially in the students, then the infrastructure, facilities and infrastructure other infrastructure. This SLB is in accordance with its vision and mission to prioritize student independence, then the Pembina SLB program is prioritized on student skills. If in percentage then, Academic (30%) and Skills (70%). To achieve goals, targets, With this vision and mission, it is necessary to develop skills for SLB students. The problems contained in the Pembina State SLB Pekanbaru are: 1) The results of the Agricultural skills are not maximized, 2) Agricultural skills are not yet based on IT and 3) Lack of knowledge of teachers and students related to IT-based Product Marketing Management. Based on these problems, the solutions offered include: 1) Will be carried out guidance to increase students' knowledge in agricultural skills, 2) Will implement IoT-based Hydroponic plant cultivation and 3) provide counseling, training and guidance to students how to do management marketing of products produced with IT.